Pelatihan Pengelasan Untuk Siswa sebagai Media Pembelajaran Kewirausahaan di SMK Muhammadiyah 1 Malang - Elka Faizal; Sugeng Hadi Susilo; Achmad Walid; Eko Yudiyanto; Gumono (CV. Creative Tugu Pena, 2024)
In learning in the field of entrepreneurship at SMKM 1 Malang it is written about basic competencies, namely demonstrating scientific behavior. Some of the problems in realizing scientific behavior in entrepreneurship learning are the limited practicum teaching aids in partner schools. For example, for learning welding methods using electric welding. Besides that, students' knowledge about welding is still lacking and there are no welding machines available at SMKM 1 Malang. This needs to be improved by providing more teaching aids with a touch of the latest technology so that it can increase students' learning capacity, especially regarding welding. The community service activities proposed through this scheme will be implemented in several stages including: (1) Carrying out training for students on welding techniques; (2) Providing welding machine facilities for learning welding at vocational schools; (3) Provide assistance in welding learning so that the expected learning outcomes are obtained, namely fostering scientific, creative, innovative behavior and high curiosity; (4) Evaluate the output and outcomes by giving practical assignments and questionnaires to students related to the entrepreneurial learning model using an electric welding machine.